2020
DOI: 10.3390/cancers12040815
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Respiration in KRAS and BRAF Mutated Colorectal Tumors and Polyps

Abstract: This study aimed to characterize the ATP-synthesis by oxidative phosphorylation in colorectal cancer (CRC) and premalignant colon polyps in relation to molecular biomarkers KRAS and BRAF. This prospective study included 48 patients. Resected colorectal polyps and postoperative CRC tissue with adjacent normal tissue (control) were collected. Patients with polyps and CRC were divided into three molecular groups: KRAS mutated, BRAF mutated and KRAS/BRAF wild-type. Mitochondrial respiration in permeabilized tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
3
19
1
Order By: Relevance
“…Our recent studies revealed remarkable differences in the regulation of outer mitochondrial membrane (OMM) permeability between cultured tumor cells and clinical material from cancer patients ( 5 , 43 ). Comparative analysis of the biopsy or surgical cancer material and surrounding healthy tissue showed almost unchanged glycolytic activity and upregulation of OXPHOS in CRC, which is inconsistent with the data obtained by using cell culture ( 43 47 ). In addition, two widely used breast cancer cell lines MCF7 and MCF-MDA-231 failed to replicate mitochondrial function in respect to metabolic activity and OXPHOS as seen in respective human samples ( 43 , 46 ).…”
Section: Metabolic Reprogramming Of Colorectal Cancercontrasting
confidence: 88%
See 2 more Smart Citations
“…Our recent studies revealed remarkable differences in the regulation of outer mitochondrial membrane (OMM) permeability between cultured tumor cells and clinical material from cancer patients ( 5 , 43 ). Comparative analysis of the biopsy or surgical cancer material and surrounding healthy tissue showed almost unchanged glycolytic activity and upregulation of OXPHOS in CRC, which is inconsistent with the data obtained by using cell culture ( 43 47 ). In addition, two widely used breast cancer cell lines MCF7 and MCF-MDA-231 failed to replicate mitochondrial function in respect to metabolic activity and OXPHOS as seen in respective human samples ( 43 , 46 ).…”
Section: Metabolic Reprogramming Of Colorectal Cancercontrasting
confidence: 88%
“…Determined in permeabilized cells and tissues, Km(ADP) is the affinity of the mitochondria for exogenous ADP and characterizes permeability of OMM for adenine nucleotides and, thus, VDAC permeability. Measured Km(ADP) values for human colon mucosa is ~110 µM ( 47 ), ~100 µM for CRC ( 5 , 44 , 47 ), ~60 µM for colon polyps ( 47 ), and ~40 µM for Caco2 CRC cell line ( 43 ), indicating the alteration of control mechanisms over VDAC permeability and OXPHOS during the progression of CRC. Thus, the regulation of OMM permeability to adenine nucleotides in cancer tissues is different from that in normal cells ( 5 , 67 , 68 ).…”
Section: The Role Of Vdac and The Regulation Of Outer Mitochondrial Membrane Permeability In Metabolic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…The mtDNA copy number was shown to be significantly lower in BRAF -mutated and microsatellite-instable (MSI) tumors and higher in KRAS -mutated tumors [ 37 ]. In accordance with this, the functional examination of the adenosine diphosphate (ADP)-activated respiration rate (Vmax) and the mitochondrial outer membrane (MOM) permeability in patient-derived KRAS -/ BRAF -mutated as well as wild-type tumor specimen indicates that KRAS mutations might be linked to an oxidative phenotype, while BRAF mutations to a glycolytic phenotype [ 38 ]. This observation may contradict the findings in another study that revealed the induction of glycolysis, the accumulation of lactic acid and the sensitivity to glycolytic inhibition in KRAS -mutated CRC cells, whereas BRAF -mutated CRC cells remained resistant towards the alterations of glucose supply or metabolic inhibitors [ 39 ].…”
Section: Mitochondrial Metabolism Of Colorectal Cancermentioning
confidence: 99%
“…Furthermore, the different subgroups of CRC by molecular types demonstrated distinct types of energy metabolism. In the BRAF or KRAS mutated tumors, metabolic reprogramming shifts from OXPHOS to a more glycolytic type [174].…”
Section: Energy Metabolism In Colorectal Cancer (Crc)mentioning
confidence: 99%